(untitled) (Journal of Oriental Studies, 2018)
The article deals with the formation and development of bilateral relations between Kazakhstan and Japan since the period of gaining independence. Over more than 20 years of cooperation, Kazakhstan and Japan have achieved positive results in various fields. In the multi-vector policy of Kazakhstan, an important place is occupied by Japan. This is due to many factors. Japan is a powerful economic power of the modern world. The cooperation of Kazakhstan with the country of the Rising Sun has opened the way for us to mutually beneficial partnership with the countries of the Asia-Pacific region. These relations have moved to the level of strategic partnership, which demonstrates the growing role of Japan in Kazakhstan’s foreign policy. And so this topic is of interest to scientists. The article examines not only the peculiarities of the development of bilateral relations between the RK and Japan, but also analyzes from the point of view of the doctrinal approach the most important concepts of the Japanese leadership and dialogues like «Central Asia plus Japan».